Rescuing ocular development in an anophthalmic pig by blastocyst complementation. Issue 12 (16th November 2018) - Zhang, Hongyong; Huang, Jiaojiao; Li, Zechen; Qin, Guosong; Zhang, Nan; Hai, Tang; Hong, Qianlong; Zheng, Qiantao; Zhang, Ying; Song, Ruigao; Yao, Jing; Cao, Chunwei; et al.
Abstract: Porcine‐derived xenogeneic sources for transplantation are a promising alternative strategy for providing organs for treatment of end‐stage organ failure in human patients because of the shortage of human donor organs. The recently developed blastocyst or pluripotent stem cell (PSC) complementation strategy opens a new route for regenerating allogenic organs in miniature pigs. Since the eye is a complicated organ with highly specialized constituent tissues derived from different primordial cell lineages, the development of an intact eye from allogenic cells is a challenging task. Here, combining somatic cell nuclear transfer technology (SCNT) and an anophthalmic pig model ( MITF L 247S/L247S ), allogenic retinal pigmented epithelium cells (RPEs) were retrieved from an E60 chimeric fetus using blastocyst complementation. Furthermore, all structures were successfully regenerated in the intact eye from the injected donor blastomeres. These results clearly demonstrate that not only differentiated functional somatic cells but also a disabled organ with highly specialized constituent tissues can be generated from exogenous blastomeres when delivered to pig embryos with an empty organ niche. This system may also provide novel insights into ocular organogenesis. Synopsis: Blastocyst complementation is a new route for regenerating allogeneic organs in pigs for xenotransplantation, but reconstituting complicated organs, like a whole eye, was never done up to now. This strategy offers potentials for generating personalized human patient‐specific organs in large animals. Intact allogenic eyes can be regenerated using exogenous blastocyst complementation in an anophthalmic pig model. Porcine RPEs are isolated and cultured in vitro from 60‐day chimeric foetuses. The chimeric pig with regenerated eyes was derived from the somatic cloned blastocyst complementation and developed to full term. Abstract : Blastocyst complementation is a new route for regenerating allogeneic organs in pigs for xenotransplantation, but reconstituting complicated organs, like a whole eye, was never done up to now. This strategy offers potentials for generating personalized human patient‐specific organs in large animals.